Structure of the GTP Form of Elongation Factor 4 (EF4) Bound to the Ribosome - Kumar, Veerendra (2017)
Elongation factor 4 (EF4) is a member of the family of ribosome-dependent translational GTPase factors, along with elongation factor G and BPI-inducible protein A. Although EF4 is highly conserved in bacterial, mitochondrial, and chloroplast genomes, its exact biological function remains controversial. Here we present the cryo-EM reconstitution of the GTP form of EF4 bound to the ribosome with P and E site tRNAs at 3.8-Å resolution. Interestingly, our structure reveals an unrotated ribosome rather than a clockwise-rotated ribosome, as observed in the presence of EF4-GDP and P site tRNA. In addition, we also observed a counterclockwise-rotated form of the above complex at 5.7-Å resolution. Taken together, our results shed light on the interactions formed between EF4, the ribosome, and the P site tRNA and illuminate the GTPase activation mechanism at previously unresolved detail.